Cancer‐Selective Supramolecular Chemotherapy by Disassembly‐Assembly Approach. (3rd October 2022) - Jeena, M. T.; Jin, Seongeon; Jeong, Keunsoo; Cho, Yuri; Kim, Jin Chul; Lee, Jeong Hyeon; Lee, Seokyoung; Hwang, Suk‐Won; Kwak, Sang Kyu; Kim, Sehoon; Ryu, Ja‐Hyoung
Abstract: Intramitochondrial supramolecular assembly can be a new therapeutic strategy for treating cancer because mitochondria are the key for virtually all facets of the tumorigenesis. However, the in vivo applications of mitochondria‐targeting molecules are limited due to the positive charge and hydrophobicity that should be possessed by these molecules to penetrate the mitochondrial membrane, which may induce nonspecific serum protein interactions and normal cell accumulation. Herein, a stimuli‐responsive mitochondria‐targeting molecule, Mito‐SA that forms nano‐sized micelles under physiological conditions is presented. In the aggregated state, the succinic amide bonds in Mito‐SA are cleaved in response to tumoral pH by stabilizing the transition state through the intermolecular interactions and the micelle disassembles into a mitochondria‐targeting parent molecule, Mito‐FF. The Mito‐FF accumulate inside cancer mitochondria to induce cell death by intra‐mitochondrial self‐assembly into fiber structures. This tumoral stimuli‐responsive disassembly–assembly approach will provide insight to develop mitochondria targeted supramolecular anticancer agent with high tumoral specificity. Abstract : Assembly‐disassembly approach for selective cancer therapy. Tumoral pH sensitive micelle of mitochondria targeted agent is constructed. The physiologically stable micelles undergo dis‐assembly into the parental molecules near the tumor that selectively diffuse into the cancer cells and induces intra‐mitochondrial self‐assembly that lead to mitochondrial damage and cell death.